Surveillance of Patients in the Waiting Area of the Department of Emergency Medicine. Issue 51 (December 2015) - Hubner, Pia; Schober, Andreas; Sterz, Fritz; Stratil, Peter; Wallmueller, Christian; Testori, Christoph; Grassmann, Daniel; Lebl, Nitaya; Ohrenberger, Iris; Herkner, Harald; Weiser, Chirstoph
Abstract : Abstract: Many patients visiting an emergency department are in reduced general condition of health and at risk of suffering further deterioration during their stay. We wanted to test the feasibility of a new monitoring system in a waiting area of an emergency department. In an observational cross-sectional single-center study, patients with acute cardiac or pulmonary symptoms or in potentially life-threatening conditions were enrolled. Monitoring devices providing vital signs via short range radio (SRR) at certain time points and compliance evaluation forms were used. Out of 230 patients, 4 wanted to terminate their participation prematurely. No data was lost due to technical difficulties. Over a median monitoring period of 178 (118–258) min per patient, 684 h of vital sign data were collected and used to assist managing those patients. Linear regression analysis between clinical symptom category groups of patients showed significant differences in the respiratory rate and noninvasive blood pressure courses. Feedback from patients and users via questionnaires showed overall very good acceptance and patients felt that they were given better care. To assist medical staff of an emergency department waiting area to rapidly response to potentially life-threatening situations of its patients, a new monitoring system proved to be feasible and safe.